The Utilization of Abacus Media in Mathematics Learning to Increase the Attractiveness and Learning Students’ Motivation - Muhammad Nasrul Haq (Journal of Educational Studies, 2025)
This study aims to describe the use of Abacus media in mathematics learning and analyze its influence on the attractiveness and learning motivation of students. This study uses a qualitative descriptive method with 22 research subjects in class V in the 2025/2026 school year. Data was collected through observation, interviews, learning outcome tests, and documentation, then analyzed in a qualitative descriptive manner with reduction steps, data presentation, and conclusion drawn. The results of the study show that the application of Abacus media in mathematics learning can increase students' interest, motivation, and active participation. Prior to the use of Abacus, most students lacked enthusiasm, were passive, and had difficulty understanding the concept of place values as well as basic calculation operations. However, after applying learning with Abacus, students become more enthusiastic, actively ask questions, dare to try, and can understand the material more easily. The average score of learning outcomes increased from 68.5 to 83.5, with classical completeness reaching 90%, and the level of learning activity increased from 60% to 88%. Thus, the use of Abacus media has proven to be effective in bridging abstract mathematical concepts into concrete, as well as creating a more interesting, fun, and motivating learning atmosphere for students to actively learn.